GranDIHC-BR 2025-2035 - GC6: Implications of Artificial Intelligence in HCI: A Discussion on Paradigms, Ethics, and Diversity, Equity and Inclusion - Duarte, Emanuel Felipe; Toledo Palomino, Paula; Pontual Falcão, Taciana; Porto, Grace Lis Proença Meireles Barreto; Portela, Carlos dos Santos; Ribeiro, Douglas Francisco; Nascimento, André; Costa Aguiar, Yuska Paola; Souza, Maurício; Moutin Segoria Gasparotto, Angelita; Maciel Toda, Armando (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
In the contemporary context of Human-Computer Interaction (HCI), new paradigms emerge that redefine the boundaries between human and artificial intelligences, prompting deep reflection on inclusion, accessibility, and equity. This article addresses the grand challenge of the implications of Artificial Intelligence (AI) in HCI, highlighting the importance of considering three main themes: interfaces and interaction paradigms; ethical approaches and design; and the promotion of equity, diversity, and inclusion. To tackle this challenge, we propose a research agenda in Brazil that encompasses short, medium, and long-term actions aimed at fostering AI development that is socially conscious and critical. We conclude by emphasizing the need to promote a profound understanding of AI's effects on society through an integrated and multifaceted approach, aligned with human values. We invite the entire HCI community to collaborate in this effort, seeking to research and develop AI interfaces that enrich human interactions in an ethical and inclusive manner. This grand challenge paper is presented in two languages, first in English and then in Brazilian Portuguese.